Exploring the Concept of Parental Influence and Its Consequences in Alex Michaelides’s The Silent Patient - S. Banupriya; B. R. Aravind (Recent Trends in Social Studies, 2024)
The present paper explores the relationship between attachment theory, parental alienation (PA), and the Parental Acceptance and Rejection Theory (PART), as illustrated by Theo Faber and Alicia Berenson in "The Silent Patient." The definition of PA and its effects on child development are covered first, with a focus on the importance of attachment types and parental involvement. Echoing the conclusions of attachment theorists and empirical research, the essay emphasizes how insufficient parental care can result in attachment anxieties and emotional dysregulation. Moving on to PART, it delves into the aspects of parental approval and disapproval, elucidating how parental actions mold kids' identities and coping strategies. The essay demonstrates how these early dynamics materialize in maladaptive behaviours and psychological disorders in adulthood by analysing Theo and Alicia's painful childhood experiences, especially parental rejection and neglect. This emphasizes the significant influence of parenting on personal development by drawing comparisons between theoretical frameworks and real-life stories. This aligns with Theo Faber's claim that our personalities are created by invisible influences, primarily our parents. The importance of PART is reaffirmed in the conclusion, along with its significance in comprehending the intricacies of familial relationships and their long-term effects on mental health and general wellbeing. All things considered, this abstract clarifies the significant impact of family dynamics on psychological adjustment and personality development by combining intricate theories with narrative representations.
Keywords: Alienation; Consequences; Parental Influence; Parental Rejection; Psychological Imbalance